Аплодисменты: повесть / Людмила Гурченко - Гурченко Людмила Марковна (Память, 1987)
Экземпляры: абонемент (20240205) / Инвентарный номер: 14819 / Авт.знак: Г95 / ГРНТИ: 17.82.94 / ББК: 84(2Рос=Рус)6-44